Asthma-related deaths in Brazil: data from an ecological study - Amanda da Rocha Oliveira Cardoso; Anna Carolina Galvão Ferreira; Marcelo Fouad Rabahi (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: The aim of this study was to present epidemiological data on hospitalizations and deaths related to asthma in Brazil over the past 11 years. Methods: An ecological study was conducted on asthma-related hospitalizations and mortality in Brazil from 2013 to 2023, using data extracted from the Department of Informatics of the Brazilian Unified Health System and the Mortality Information System. Results: Asthma-related deaths showed an increasing trend during the analyzed period. A surge in deaths was observed in 2022 compared to 2014 (difference between means = 56.08 ± 19.7; 95% CI = 15.2-96.9). The mean number of deaths was higher among females, with their rate remaining stable, while the rate for males increased. Individuals aged >60 years accounted for approximately 65% of all asthma-related deaths from 2013 to 2023, with a strong direct correlation observed between age and the number of deaths, regardless of sex. During the same period, the total number of asthma-related hospitalizations in Brazil showed a declining trend, decreasing from 134,322 in 2013 to 87,707 in 2023. Conclusion: Over the past 11 years, asthma-related deaths have increased in Brazil, with the majority occurring among females. Older individuals accounted for most asthma-related deaths, and a positive correlation was observed between age and the number of deaths.